2013
DOI: 10.1111/mice.12011
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Local Linear Model Tree Approach to Car‐Following

Abstract: Because car‐following (CF) models are fundamental to replicating traffic flow they have received considerable attention over the last 50 years. They are in a continuous state of improvement due to their significant role in traffic microsimulations, intelligent transportation systems, and safety engineering models. This article uses the local linear model tree (LOLIMOT) approach to model driver's CF behavior to incorporate human perceptual imperfections into a CF model. This model defines some localities in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Therefore, it is necessary to consider the relationship between the coupled vehicle group and its surrounding environment, i.e., those vehicles in the front and rear of the group that cannot be coupled into the system because of the lack of V2V or automated control capability. Under actual traffic conditions, the coupled group is usually heterogeneous rather than homogeneous, and the group is generally comprised of vehicles of different masses, lengths, and braking systems operated by drivers exhibiting a variety of car-following [3,30] and lane-changing behaviors [33]. The heterogeneous nature of a coupled group can seriously affect platoon control [24] and also the capacity of signalized intersections [40].…”
Section: Preview Of Key Resultsmentioning
confidence: 99%
“…Therefore, it is necessary to consider the relationship between the coupled vehicle group and its surrounding environment, i.e., those vehicles in the front and rear of the group that cannot be coupled into the system because of the lack of V2V or automated control capability. Under actual traffic conditions, the coupled group is usually heterogeneous rather than homogeneous, and the group is generally comprised of vehicles of different masses, lengths, and braking systems operated by drivers exhibiting a variety of car-following [3,30] and lane-changing behaviors [33]. The heterogeneous nature of a coupled group can seriously affect platoon control [24] and also the capacity of signalized intersections [40].…”
Section: Preview Of Key Resultsmentioning
confidence: 99%
“…In order to simulate the features of traffic flow, different kinds of models have been proposed, such as the carfollowing models (Chandler et al 1958;Rakha and Crowther, 2003;Kesting and Treiber, 2008;Aghabayk et al 2013), the cellular automata models Hafstein et al, 2004) and hydrodynamic models (Lighthill and Whitham, 1955;Papageorgiou 1998;Wong and Wong 2002).…”
Section: Discussionmentioning
confidence: 99%
“…One type is macroscopic traffic flow models, which treat traffic as a compressive fluid and capture traffic behaviors using macroscopic parameters, including flow, density, and velocity (Bagloee et al, 2017;Mehrabipour and Hajbabaie, 2017). The other type is microscopic traffic flow models, such as carfollowing models (Woods and Berg, 2001;Aghabayk et al, 2013;Pariota et al, 2015;Li et al, 2018), lanechanging models (Gipps, 1986;Jula et al, 2000;Hidas, 2002), and cellular automation (Ding et al, 2009;Duff et al, 2015;Crociani and Lämmel, 2016) which can describe traffic dynamics at a higher detailed level like movements of individual vehicles. Previous studies (e.g., Kim et al, 2018) suggested to use macroscopic models, such as cell transmission model (CTM), to describe traffic behaviors.…”
Section: The Physical Layer: a Traffic Flow Modelmentioning
confidence: 99%